PENINGKATAN HASIL BELAJAR SISWA KELAS V DENGAN MODEL PEMBELAJARAN SAVI PADA MATA PELAJARAN IPA DI SDN MANGKUJAYAN I KABUPATEN PONOROGO - Kusumawati, Naniek (JURNAL PENDIDIKAN DASAR NUSANTARA, 2018)
The result of observation in state elementary school Mangkujayan I at learning process on 5th grade which is still conventional so student’s mindset’s development and creativity is less. There are some teachers especially 5th grade’s teachers which only tell the learning material to the students and the students only listen, make a note and memorize the material. This study aims to improve student learning outcomes, especially on science subjects class V using SAVI learning model. This research uses classroom action research or CAR. This research procedure uses four steps of cycle such as planning, implementating, observing and reflecting step. Data collection technique is cognitive test and data collection instrument is test and observation instrument. Analysis of the data obtained shows that there is an increase in student learning outcomes that can be seen from the average percentage of the results in the first cycle is 65% which means there are 13 of 20 students who complete. There is 90% increasing on second cycle which means 18 of 20 students who can be succes on learning. Based on the research result, it can be concluded that the implementation of SAVI learning model can increase the study performance of students on natural studies of 5th grade of SDN Mangkujayan I. Keywords: SAVI learning models, study performance IPA.